Increased alveolar/capillary membrane resistance to gas transfer in patients with chronic heart failure. Issue 2 (August 1994) - Puri, S; Baker, B L; Oakley, C M; Hughes, J M; Cleland, J G
Abstract : OBJECTIVE--To investigate pulmonary diffusive resistance to gas exchange in patients with heart failure and healthy volunteers, assessing the relative contributions of the alveolar/capillary membrane and pulmonary capillary blood. SETTING--Hospital outpatient department and pulmonary function laboratory. PATIENTS--38 patients (mean age 60) receiving treatment with loop diuretics and angiotensin converting enzyme inhibitors for stable symptomatic heart failure of > 6 months duration (New York Heart Association (NYHA) classes II and III). Results were compared with those of 17 healthy volunteers (mean age 52). METHODS--The alveolar/capillary membrane diffusive resistance and the pulmonary capillary blood volume available for physiological gas exchange were determined by the Roughton and Forster method, which measures the single breath pulmonary diffusing capacity for carbon monoxide at varying alveolar oxygen concentrations. RESULTS--Total pulmonary diffusive resistance was higher in patients than controls. Alveolar/capillary membrane resistance formed the main component of this increase, accounting for a mean (SD) of 63% (20%) and 86% (8%) of total pulmonary diffusive resistance in patients in NYHA II and III classes respectively, compared with 53% (10%) in controls. The pulmonary capillary blood volume was not significantly different between controls and patients in NYHA class II (66 (18) ml v 61 (18) ml), but was increased in those in NYHA class III (95(46) ml, P < 0.05). CONCLUSION--This study confirmed impairment of pulmonary diffusion at rest in patients with chronic heart failure and identified impaired alveolar/capillary membrane function as the main factor responsible.